Digital watermarking scheme based on curvelet transform and multiple chaotic maps - Xiao, Yi; Xu, Ya-Chen; Zhou, Nan-Run; Lin, Zhen-Rong (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
The rapid development of digital products brings security issues. Digital watermarking technology is an important means to handle these problems. To enhance the imperceptibility of watermark and locate the possible tampering as well, a digital watermarking scheme based on curvelet transform is presented by combining with multiple chaotic maps. The host image is decomposed into three parts, i.e., coarse layer, detail layer and fine layer, with curvelet transform, and a robust watermark is embedded into the coarse layer for copyright protection of digital products. In addition, an authentication watermark is embedded into the fine layer to detect and locate the illegal changes. Simulation results show that the proposed digital watermarking scheme possesses acceptable robustness and security.
Optica Applicata, Vol. 53, 2023, nr 2, s. 291-305
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; digital watermarking; curvelet transform; multiple chaotic maps